RAT-SQL: Relation-Aware Schema Encoding and Linking for Text-to-SQL Parsers - Wang, Bailin; Shin, Richard; Liu, Xiaodong; Polozov, Alex; Richardson, Matthew (ACL 2020, 2020)
When translating natural language questions into SQL queries to answer questions from a database, contemporary semantic parsing models struggle to generalize to unseen database schemas. The generalization challenge lies in (a) encoding the database relations in an accessible way for the semantic parser, and (b) modeling alignment between database columns and their mentions in a given query. We present a unified framework, based on the relation-aware self-attention mechanism, to address schema encoding, schema linking, and feature representation within a text-to-SQL encoder. On the challenging Spider dataset this framework boosts the exact match accuracy to 53.7%, compared to 47.4% for the state-of-the-art model unaugmented with BERT embeddings. In addition, we observe qualitative improvements in the model's understanding of schema linking and alignment.